2021
DOI: 10.1017/jfm.2020.909
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent modal coupling in screeching underexpanded circular twin jets

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Nevertheless, modelling screech intermittency may not be very straightforward. For example, recent studies of intermittent screech tones generated by under-expanded twin round jets [58] suggested that this erratic behavior of screech tones were attributed to a competition between two global modes of the flow system, which are a function of the inter-nozzle spacing and NPR.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, modelling screech intermittency may not be very straightforward. For example, recent studies of intermittent screech tones generated by under-expanded twin round jets [58] suggested that this erratic behavior of screech tones were attributed to a competition between two global modes of the flow system, which are a function of the inter-nozzle spacing and NPR.…”
Section: Discussionmentioning
confidence: 99%
“…At specific nozzle spacings and Mach numbers, the coupling behaviour can become erratic, leading to periods where the jet can switch between symmetric or antisymmetric modes or uncouple entirely (Bell et al. 2021). This has been suggested to be the result of a competition between global modes of the flow, which is supported by the fact that different coupling symmetries exhibit similar growth rates and wavenumbers for the Kelvin–Helmholtz instability (Nogueira & Edgington-Mitchell 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned study by Bell et al. (2021) on twin round jets used modal decomposition of particle image velocimetry (PIV) data alongside time-frequency analysis of acoustic data to demonstrate that at some operating conditions the coupling between jets was steady, and at other conditions was highly intermittent. In rectangular twin jets intermittency has been observed both experimentally (Ghassemi Isfahani, Webb & Samimy 2021 b ) and numerically (Jeun, Wu & Lele 2021 a ; Jeun et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 5 years, twin jets screech is still a research field. Coupling modes are investigated experimentally by Kuo [16], Knast [17] or Bell [18]. On this topic, numerical simulations of previous studies start to arise (Goparaju [19] on Kuo's setup [16], Gao [20] or Anh [21] on Walker's setup [10]).…”
Section: Introductionmentioning
confidence: 99%